Project Report Automated Urban Drinking Water Supply Control and Water Theft Identification System - SWETHA JOSHI, SWETHA S, YASHASWINI N and SWATHI R (2011)
INTERNAL GUIDE : Praveena K EXTERNAL GUIDE : Pradeep kumar C USN NO : 1MJ08EC405 and 1MJ09EC094 CARRIED OUT AT : Mvj Coolege Of Engineerig Channasandra Near ITPB Bangalore-560 067 ACC NO : PR1873
Keywords: Identification System